The Phenomenon of Islamic Life in the Movement of "Roan Akbar Pesantren" into the Industrial Era - Muhammad Akrom Adabi; Neny Muthi'atul Awwaliyah (Kawanua International Journal of Multicultural Studies, 2021)
This study seeks to reveal the progression of pesantren in the development of the pesantren environment in the era industry through the Roan Akbar Movement. This research uses an interactive analysis method. Data sourced from interviews, field observations, and documentation. The research location is in Pekalongan. Research shows, through the Roan Akbar Movement, pesantren have progressive development in the environment of students. It can be seen from two things. First, the acceptance of the presence of era Industry. Second, by eradicating the negative values of the era of disruption such as reduced social sense, solidarity, and caring. The acceptance was reflected in at least three things: activities' implementation, documentation of activities, and communication patterns formed in the Roan Akbar Movement. The eliminating of negative values is realized by the massive movement of the Roan Akbar Movement, which has a positive impact on the environment in pesantren.